(untitled) (Research, Society and Development, 2022)
The reduction of consumption of animal products is a practice that has been showing an increasing number of adherents. The plant-based food pattern has nutritional properties capable of presenting health benefits. This practice favors the search for a more sustainable food system in the context of advances in globalization, industrialization, population growth and environmental impact. Considering the relevance of stimulating sustainable production and consumption, this study aimed to investigate the facilitators and limitations related to the reduction in meat consumption in the population of the Niterói city, metropolitan region of the State of Rio de Janeiro - Brazil. Data was collected by an online survey, and then disseminated through social media. Environmental issues and health benefits proved to be facilitators for reducing meat consumption.While the taste for meat is a barrier that limits its consumption reduction. Social interaction has no limiting factor, as a meat substitute. Finally, the intention to reduce meat consumption demonstrated a balance between disagreement and agreement, but there may be a chance that consumers will adhere to this dietary pattern in the future.